2008
DOI: 10.1007/s12298-008-0032-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro clonal propagation of bael (Aegle marmelos Corr.) CV. CISH-B1 through enhanced axillary branching

Abstract: Rapid clonal micropropagation protocol of Aegle marmelos (L.) Corr. cv. CISH-B1 was achieved by nodal stem segment of mature bearing tree. Three centimeter long shoots having one axillary bud excised from 10-15th nodal region of shoots during September gave quick in vitro bud burst (5.33 days) when cultured on MS medium supplemented with BAP, 8.84 μM + IAA 5.7 μM. The maximum number of proliferated shoots (9.0/explant) were obtained on same medium supplemented with BAP 8.84 μM + IAA 5.7 μM. The micro shoots we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…The results of this molecular study revealed that all the primers used in this study showed a monomorphic pattern in all the sample plants, confirming the genetic uniformity of the regenerated plantlets and that no variation was induced during in vitro propagation of A. marina (Figures 3À5). The findings of this investigation corroborate several earlier reports on genetic analysis of regenerated plantlets in Mentha arvensis, [16] Aegle marmelos, [27] Bambusa balcooa, [28] Gerbera jamesonii [29] and Gloriosa superba [30], using SPAR analysis.…”
Section: Genetic Fidelity Of Regenerated Plantssupporting
confidence: 91%
“…The results of this molecular study revealed that all the primers used in this study showed a monomorphic pattern in all the sample plants, confirming the genetic uniformity of the regenerated plantlets and that no variation was induced during in vitro propagation of A. marina (Figures 3À5). The findings of this investigation corroborate several earlier reports on genetic analysis of regenerated plantlets in Mentha arvensis, [16] Aegle marmelos, [27] Bambusa balcooa, [28] Gerbera jamesonii [29] and Gloriosa superba [30], using SPAR analysis.…”
Section: Genetic Fidelity Of Regenerated Plantssupporting
confidence: 91%
“…Earlier reports demonstrated that plant regeneration was possible through apical shoot bud, node, internodes, leaf and nucellar tissues explants (Pati et. al., 2008;Arumugam et.…”
Section: Resultsmentioning
confidence: 99%
“…al., 1982). The tree grows wild in dry forests on hills and plains of central Southern India, Burma, Pakistan, Bangladesh, Srilanka, Northern Malaya, Java and Philippine Islands (Pati et. al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Micropropagation protocol of Pati et al (2008a;2008b) was followed to regenerate plantlets of Aegle marmelos Corr.…”
Section: Explant and Growth Conditionsmentioning
confidence: 99%
“…Micropropagation technique has been developed in Aegle mormelos Corr. from mature tree through enhanced axillary branching for mass multiplication (Pati et al, 2008;Pati et al, 2008a;Pati et al, 2008b;Raj and Basavaraju, 2012). However, high mortality of micropropagated plants during acclimatization and subsequently poor field establishment remains a major bottleneck in commercealizing the micropropagation protocol to industry.…”
Section: Introductionmentioning
confidence: 99%